System and Structure of English Classroom Discourse at Junior High School in Medan - Maulidina Mutia; Masdiana Lubis; Nurlela Nurlela (Indonesian Journal of EFL and Linguistics, 2022)
This study aims to investigate the system and structure of English classroom interaction at Medan's Jabal Rahmah Mulia Boarding School. The records of a discussion in communication a video recording by Zoom Meeting among understudies and an English educator are viewed as information to be concentrated on utilizing a talk examination approach in light of Martin's Conversation Analysis (CA) model inside Halliday's Systemic Functional Linguistics structure (SFL). The foundation of the framework and construction of the English study hall connection are the challenges to be addressed. The examination saw movement types, temperament types, and the discourse capability of different provisions. The discoveries show that understudies act as initiators, while English educators work as allies, with optional knower (k2k1) moving sort for the most part; the communication is one of data exchange instead of labor and products, as conversationalists favor decisive and utilize basic sparingly. As per the discoveries, Question (Q) appears to generally satisfy the data given. Inquisitive asking is most ordinarily used to exhibit that a design's relational significance doesn't be guaranteed to compare to its lexico-sentence structure. This examination likewise shows how a study hall conversation happens in a characteristic set of mindset and discourse capability. It likewise demonstrates that understudies are on the requesting end of the scale, bringing about an absence of criticism in the communication.